High Incidence of Dyslipidemia In Obese Type 2 Diabetics (Medical Forum Monthly, 2024)
Objective: To ascertain the effect of Body Mass Index (BMI) on plasma lipid profile in type 2 diabetes mellitus (T2DM). Study design: Comparative, observational study Place and duration of study: Army Medical College, Rawalpindi from Jan 2007- June 2010. Patients and Methods: Sample size was 60, subdivided in to two groups. Group 1 comprising on 30 type 2 diabetics with BMI < 25, whereas Group 2 consisted of 30 type 2 diabetics with BMI > 28. Blood glucose, HbA1c, plasma cholesterol and triglyceride levels were determined. Results: Group 1 consisted of 56% males and 44 % females, whereas Group 2 had 54 % males and 46 % females. Mean age to develop T2DM for group 1 was 44.60 + 1.22 years and for group 2 was 42.13 + 0.86 years. BMI of group 1 was 20.29 + 0.56 and Group 2 was 28.95 + 0.26. Mean plasma cholesterol and plasma triglyceride levels of group 2 diabetics were significantly higher (p< 0.001) as compared with group 1 non obese diabetics. Whereas, mean plasma glucose (p< 0.01) and Glycosylated hemoglobin (p< 0.05) of group 2 diabetics were significantly higher as compared with group 1 non obese diabetics Conclusion: Dyslipidemia was more marked in obese type 2 diabetics. Whereas diabetics with low BMI had plasma lipid profile within normal range.